Mulheres no Big Data: um estudo sobre diversidade e inclusão na área de dados - Oliveira, Natália Gonçalves (Universidade Federal de São Carlos, 2024)
The objective of this study was to understand the challenges faced by women in the fields of Science, Technology, Engineering, and Mathematics (STEM), with a specific focus on the data field. To achieve this, interviews were conducted with seven women working in this area to gain a deeper understanding of their professional experiences and the challenges they encounter. Additionally, a literature review was performed to explore the issue of gender disparity in the labor market, along with the collection of secondary data about the data field in Brazil. The results highlight a significant impact on career progression, stress levels at work, and the receptiveness of colleagues to their opinions, all due to the fact that they are women. Furthermore, some limitations of corporate diversity policies were observed in preventing and mitigating the occurrence of discrimination and microaggressions in the workplace.
Women in Big Data: a study on diversity and inclusion in the data field
Keywords: Gênero e trabalho; Ciência e tecnologia; Big data; Carreira; Diversidade; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO; 5. Igualdade de Gênero